Algebra and Trigonometry 2e

# 9.1Verifying Trigonometric Identities and Using Trigonometric Identities to Simplify Trigonometric Expressions

Algebra and Trigonometry 2e9.1 Verifying Trigonometric Identities and Using Trigonometric Identities to Simplify Trigonometric Expressions

## Learning Objectives

In this section, you will:
• Verify the fundamental trigonometric identities.
• Simplify trigonometric expressions using algebra and the identities.
Figure 1 International passports and travel documents

In espionage movies, we see international spies with multiple passports, each claiming a different identity. However, we know that each of those passports represents the same person. The trigonometric identities act in a similar manner to multiple passports—there are many ways to represent the same trigonometric expression. Just as a spy will choose an Italian passport when traveling to Italy, we choose the identity that applies to the given scenario when solving a trigonometric equation.

In this section, we will begin an examination of the fundamental trigonometric identities, including how we can verify them and how we can use them to simplify trigonometric expressions.

## Verifying the Fundamental Trigonometric Identities

Identities enable us to simplify complicated expressions. They are the basic tools of trigonometry used in solving trigonometric equations, just as factoring, finding common denominators, and using special formulas are the basic tools of solving algebraic equations. In fact, we use algebraic techniques constantly to simplify trigonometric expressions. Basic properties and formulas of algebra, such as the difference of squares formula and the perfect squares formula, will simplify the work involved with trigonometric expressions and equations. We already know that all of the trigonometric functions are related because they all are defined in terms of the unit circle. Consequently, any trigonometric identity can be written in many ways.

To verify the trigonometric identities, we usually start with the more complicated side of the equation and essentially rewrite the expression until it has been transformed into the same expression as the other side of the equation. Sometimes we have to factor expressions, expand expressions, find common denominators, or use other algebraic strategies to obtain the desired result. In this first section, we will work with the fundamental identities: the Pythagorean identities, the even-odd identities, the reciprocal identities, and the quotient identities.

We will begin with the Pythagorean identities (see Table 1), which are equations involving trigonometric functions based on the properties of a right triangle. We have already seen and used the first of these identifies, but now we will also use additional identities.

Pythagorean Identities
$sin 2 θ+ cos 2 θ=1 sin 2 θ+ cos 2 θ=1$ $1+ cot 2 θ= csc 2 θ 1+ cot 2 θ= csc 2 θ$ $1+ tan 2 θ= sec 2 θ 1+ tan 2 θ= sec 2 θ$
Table 1

The second and third identities can be obtained by manipulating the first. The identity $1+ cot 2 θ= csc 2 θ 1+ cot 2 θ= csc 2 θ$ is found by rewriting the left side of the equation in terms of sine and cosine.

Prove: $1+ cot 2 θ= csc 2 θ 1+ cot 2 θ= csc 2 θ$

Similarly, $1+ tan 2 θ= sec 2 θ 1+ tan 2 θ= sec 2 θ$ can be obtained by rewriting the left side of this identity in terms of sine and cosine. This gives

Recall that we determined which trigonometric functions are odd and which are even. The next set of fundamental identities is the set of even-odd identities. The even-odd identities relate the value of a trigonometric function at a given angle to the value of the function at the opposite angle. (See Table 2).

Even-Odd Identities
$tan(−θ)=−tanθ cot(−θ)=−cotθ tan(−θ)=−tanθ cot(−θ)=−cotθ$ $sin(−θ)=−sinθ csc(−θ)=−cscθ sin(−θ)=−sinθ csc(−θ)=−cscθ$ $cos(−θ)=cosθ sec(−θ)=secθ cos(−θ)=cosθ sec(−θ)=secθ$
Table 2

Recall that an odd function is one in which $f(− x )= −f( x ) f(− x )= −f( x )$ for all $x x$ in the domain of $f. f.$ The sine function is an odd function because $sin( −θ )=−sinθ. sin( −θ )=−sinθ.$ The graph of an odd function is symmetric about the origin. For example, consider corresponding inputs of $π 2 π 2$ and $− π 2 . − π 2 .$ The output of $sin( π 2 ) sin( π 2 )$ is opposite the output of $sin( − π 2 ). sin( − π 2 ).$ Thus,

$sin( π 2 ) = 1 and sin( − π 2 ) = −sin( π 2 ) = −1 sin( π 2 ) = 1 and sin( − π 2 ) = −sin( π 2 ) = −1$

This is shown in Figure 2.

Figure 2 Graph of $y=sinθ y=sinθ$

Recall that an even function is one in which

The graph of an even function is symmetric about the y-axis. The cosine function is an even function because $cos(−θ)=cosθ. cos(−θ)=cosθ.$ For example, consider corresponding inputs $π 4 π 4$ and $− π 4 . − π 4 .$ The output of $cos( π 4 ) cos( π 4 )$ is the same as the output of $cos( − π 4 ). cos( − π 4 ).$ Thus,

$cos( − π 4 ) = cos( π 4 ) ≈ 0.707 cos( − π 4 ) = cos( π 4 ) ≈ 0.707$

See Figure 3.

Figure 3 Graph of $y=cosθ y=cosθ$

For all $θ θ$ in the domain of the sine and cosine functions, respectively, we can state the following:

• Since $sin(−θ )=−sinθ, sin(−θ )=−sinθ,$ sine is an odd function.
• Since, $cos(− θ )=cosθ, cos(− θ )=cosθ,$ cosine is an even function.

The other even-odd identities follow from the even and odd nature of the sine and cosine functions. For example, consider the tangent identity, $tan(− θ )=−tanθ. tan(− θ )=−tanθ.$ We can interpret the tangent of a negative angle as $tan(− θ )= sin( −θ ) cos(− θ ) = −sinθ cosθ =−tanθ. tan(− θ )= sin( −θ ) cos(− θ ) = −sinθ cosθ =−tanθ.$ Tangent is therefore an odd function, which means that $tan( −θ )=−tan( θ ) tan( −θ )=−tan( θ )$ for all $θ θ$ in the domain of the tangent function.

The cotangent identity, $cot( −θ )=−cotθ, cot( −θ )=−cotθ,$ also follows from the sine and cosine identities. We can interpret the cotangent of a negative angle as $cot( −θ )= cos( −θ ) sin( −θ ) = cosθ −sinθ =−cotθ. cot( −θ )= cos( −θ ) sin( −θ ) = cosθ −sinθ =−cotθ.$ Cotangent is therefore an odd function, which means that $cot( −θ )=−cot( θ ) cot( −θ )=−cot( θ )$ for all $θ θ$ in the domain of the cotangent function.

The cosecant function is the reciprocal of the sine function, which means that the cosecant of a negative angle will be interpreted as $csc( −θ )= 1 sin( −θ ) = 1 −sinθ =−cscθ. csc( −θ )= 1 sin( −θ ) = 1 −sinθ =−cscθ.$ The cosecant function is therefore odd.

Finally, the secant function is the reciprocal of the cosine function, and the secant of a negative angle is interpreted as $sec( −θ )= 1 cos( −θ ) = 1 cosθ =secθ. sec( −θ )= 1 cos( −θ ) = 1 cosθ =secθ.$ The secant function is therefore even.

To sum up, only two of the trigonometric functions, cosine and secant, are even. The other four functions are odd, verifying the even-odd identities.

The next set of fundamental identities is the set of reciprocal identities, which, as their name implies, relate trigonometric functions that are reciprocals of each other. See Table 3. Recall that we first encountered these identities when defining trigonometric functions from right angles in Right Angle Trigonometry.

Reciprocal Identities
$sinθ= 1 cscθ sinθ= 1 cscθ$ $cscθ= 1 sinθ cscθ= 1 sinθ$
$cosθ= 1 secθ cosθ= 1 secθ$ $secθ= 1 cosθ secθ= 1 cosθ$
$tanθ= 1 cotθ tanθ= 1 cotθ$ $cotθ= 1 tanθ cotθ= 1 tanθ$
Table 3

The final set of identities is the set of quotient identities, which define relationships among certain trigonometric functions and can be very helpful in verifying other identities. See Table 4.

Quotient Identities
$tanθ= sinθ cosθ tanθ= sinθ cosθ$ $cotθ= cosθ sinθ cotθ= cosθ sinθ$
Table 4

The reciprocal and quotient identities are derived from the definitions of the basic trigonometric functions.

## Summarizing Trigonometric Identities

The Pythagorean identities are based on the properties of a right triangle.

$cos 2 θ+ sin 2 θ=1 cos 2 θ+ sin 2 θ=1$
$1+ cot 2 θ= csc 2 θ 1+ cot 2 θ= csc 2 θ$
$1+ tan 2 θ= sec 2 θ 1+ tan 2 θ= sec 2 θ$

The even-odd identities relate the value of a trigonometric function at a given angle to the value of the function at the opposite angle.

$tan( −θ )=−tanθ tan( −θ )=−tanθ$
$cot( −θ )=−cotθ cot( −θ )=−cotθ$
$sin( −θ )=−sinθ sin( −θ )=−sinθ$
$csc( −θ )=−cscθ csc( −θ )=−cscθ$
$cos( −θ )=cosθ cos( −θ )=cosθ$
$sec( −θ )=secθ sec( −θ )=secθ$

The reciprocal identities define reciprocals of the trigonometric functions.

$sinθ= 1 cscθ sinθ= 1 cscθ$
$cosθ= 1 secθ cosθ= 1 secθ$
$tanθ= 1 cotθ tanθ= 1 cotθ$
$cscθ= 1 sinθ cscθ= 1 sinθ$
$secθ= 1 cosθ secθ= 1 cosθ$
$cotθ= 1 tanθ cotθ= 1 tanθ$

The quotient identities define the relationship among the trigonometric functions.

$tanθ= sinθ cosθ tanθ= sinθ cosθ$
$cotθ= cosθ sinθ cotθ= cosθ sinθ$

## Example 1

### Graphing the Equations of an Identity

Graph both sides of the identity $cotθ= 1 tanθ . cotθ= 1 tanθ .$ In other words, on the graphing calculator, graph $y=cotθ y=cotθ$ and $y= 1 tanθ . y= 1 tanθ .$

### Analysis

We see only one graph because both expressions generate the same image. One is on top of the other. This is a good way to confirm an identity verified with analytical means. If both expressions give the same graph, then they are most likely identities.

## How To

Given a trigonometric identity, verify that it is true.

1. Work on one side of the equation. It is usually better to start with the more complex side, as it is easier to simplify than to build.
2. Look for opportunities to factor expressions, square a binomial, or add fractions.
3. Noting which functions are in the final expression, look for opportunities to use the identities and make the proper substitutions.
4. If these steps do not yield the desired result, try converting all terms to sines and cosines.

## Example 2

### Verifying a Trigonometric Identity

Verify $tanθcosθ=sinθ. tanθcosθ=sinθ.$

### Analysis

This identity was fairly simple to verify, as it only required writing $tanθ tanθ$ in terms of $sinθ sinθ$ and $cosθ. cosθ.$

## Try It #1

Verify the identity $cscθcosθtanθ=1. cscθcosθtanθ=1.$

## Example 3

### Verifying the Equivalency Using the Even-Odd Identities

Verify the following equivalency using the even-odd identities:

$( 1+sinx )[ 1+sin( −x ) ]= cos 2 x ( 1+sinx )[ 1+sin( −x ) ]= cos 2 x$

## Example 4

### Verifying a Trigonometric Identity Involving sec2θ

Verify the identity $sec 2 θ−1 sec 2 θ = sin 2 θ sec 2 θ−1 sec 2 θ = sin 2 θ$

### Analysis

In the first method, we used the identity $sec 2 θ= tan 2 θ+1 sec 2 θ= tan 2 θ+1$ and continued to simplify. In the second method, we split the fraction, putting both terms in the numerator over the common denominator. This problem illustrates that there are multiple ways we can verify an identity. Employing some creativity can sometimes simplify a procedure. As long as the substitutions are correct, the answer will be the same.

## Try It #2

Show that $cotθ cscθ =cosθ. cotθ cscθ =cosθ.$

## Example 5

### Creating and Verifying an Identity

Create an identity for the expression $2tanθsecθ 2tanθsecθ$ by rewriting strictly in terms of sine.

## Example 6

### Verifying an Identity Using Algebra and Even/Odd Identities

Verify the identity:

$sin 2 ( −θ )− cos 2 ( −θ ) sin( −θ )−cos( −θ ) =cosθ−sinθ sin 2 ( −θ )− cos 2 ( −θ ) sin( −θ )−cos( −θ ) =cosθ−sinθ$

## Try It #3

Verify the identity $sin 2 θ−1 tanθsinθ−tanθ = sinθ+1 tanθ . sin 2 θ−1 tanθsinθ−tanθ = sinθ+1 tanθ .$

## Example 7

### Verifying an Identity Involving Cosines and Cotangents

Verify the identity: $( 1− cos 2 x )( 1+ cot 2 x )=1. ( 1− cos 2 x )( 1+ cot 2 x )=1.$

## Using Algebra to Simplify Trigonometric Expressions

We have seen that algebra is very important in verifying trigonometric identities, but it is just as critical in simplifying trigonometric expressions before solving. Being familiar with the basic properties and formulas of algebra, such as the difference of squares formula, the perfect square formula, or substitution, will simplify the work involved with trigonometric expressions and equations.

For example, the equation $( sinx+1 )( sinx−1 )=0 ( sinx+1 )( sinx−1 )=0$ resembles the equation $( x+1 )( x−1 )=0, ( x+1 )( x−1 )=0,$ which uses the factored form of the difference of squares. Using algebra makes finding a solution straightforward and familiar. We can set each factor equal to zero and solve. This is one example of recognizing algebraic patterns in trigonometric expressions or equations.

Another example is the difference of squares formula, $a 2 − b 2 =( a−b )( a+b ), a 2 − b 2 =( a−b )( a+b ),$ which is widely used in many areas other than mathematics, such as engineering, architecture, and physics. We can also create our own identities by continually expanding an expression and making the appropriate substitutions. Using algebraic properties and formulas makes many trigonometric equations easier to understand and solve.

## Example 8

### Writing the Trigonometric Expression as an Algebraic Expression

Write the following trigonometric expression as an algebraic expression: $2 cos 2 θ+cosθ−1. 2 cos 2 θ+cosθ−1.$

## Example 9

### Rewriting a Trigonometric Expression Using the Difference of Squares

Rewrite the trigonometric expression using the difference of squares: $4 cos 2 θ−1. 4 cos 2 θ−1.$

### Analysis

If this expression were written in the form of an equation set equal to zero, we could solve each factor using the zero factor property. We could also use substitution like we did in the previous problem and let $cosθ=x, cosθ=x,$ rewrite the expression as $4 x 2 −1, 4 x 2 −1,$ and factor $( 2x−1 )( 2x+1 ). ( 2x−1 )( 2x+1 ).$ Then replace $x x$ with $cosθ cosθ$ and solve for the angle.

## Try It #4

Rewrite the trigonometric expression using the difference of squares: $25−9 sin 2 θ. 25−9 sin 2 θ.$

## Example 10

### Simplify by Rewriting and Using Substitution

Simplify the expression by rewriting and using identities:

$csc 2 θ− cot 2 θ csc 2 θ− cot 2 θ$

## Try It #5

Use algebraic techniques to verify the identity: $cosθ 1+sinθ = 1−sinθ cosθ . cosθ 1+sinθ = 1−sinθ cosθ .$

(Hint: Multiply the numerator and denominator on the left side by $1−sinθ.) 1−sinθ.)$

## Media

Access these online resources for additional instruction and practice with the fundamental trigonometric identities.

## 9.1 Section Exercises

### Verbal

1.

We know $g(x)=cosx g(x)=cosx$ is an even function, and $f(x)=sinx f(x)=sinx$ and $h(x)=tanx h(x)=tanx$ are odd functions. What about $G(x)= cos 2 x,F(x)= sin 2 x, G(x)= cos 2 x,F(x)= sin 2 x,$ and $H(x)= tan 2 x? H(x)= tan 2 x?$ Are they even, odd, or neither? Why?

2.

Examine the graph of $f(x)=secx f(x)=secx$ on the interval $[−π,π]. [−π,π].$ How can we tell whether the function is even or odd by only observing the graph of $f(x)=secx? f(x)=secx?$

3.

After examining the reciprocal identity for $sect, sect,$ explain why the function is undefined at certain points.

4.

All of the Pythagorean identities are related. Describe how to manipulate the equations to get from $sin 2 t+ cos 2 t=1 sin 2 t+ cos 2 t=1$ to the other forms.

### Algebraic

For the following exercises, use the fundamental identities to fully simplify the expression.

5.

$sinxcosxsecx sinxcosxsecx$

6.

$sin(−x)cos(−x)csc(−x) sin(−x)cos(−x)csc(−x)$

7.

$tanxsinx+secx cos 2 x tanxsinx+secx cos 2 x$

8.

$cscx+cosxcot(−x) cscx+cosxcot(−x)$

9.

$cott+tant sec(−t) cott+tant sec(−t)$

10.

$3 sin 3 tcsct+ cos 2 t+2cos(−t)cost 3 sin 3 tcsct+ cos 2 t+2cos(−t)cost$

11.

$−tan(−x)cot(−x) −tan(−x)cot(−x)$

12.

$−sin(−x)cosxsecxcscxtanx cotx −sin(−x)cosxsecxcscxtanx cotx$

13.

$1+ tan 2 θ csc 2 θ + sin 2 θ+ 1 sec 2 θ 1+ tan 2 θ csc 2 θ + sin 2 θ+ 1 sec 2 θ$

14.

$( tanx csc 2 x + tanx sec 2 x )( 1+tanx 1+cotx )− 1 cos 2 x ( tanx csc 2 x + tanx sec 2 x )( 1+tanx 1+cotx )− 1 cos 2 x$

15.

$1− cos 2 x tan 2 x +2 sin 2 x 1− cos 2 x tan 2 x +2 sin 2 x$

For the following exercises, simplify the first trigonometric expression by writing the simplified form in terms of the second expression.

16.

$tanx+cotx cscx ;cosx tanx+cotx cscx ;cosx$

17.

$secx+cscx 1+tanx ;sinx secx+cscx 1+tanx ;sinx$

18.

$cosx 1+sinx +tanx;cosx cosx 1+sinx +tanx;cosx$

19.

$1 sinxcosx −cotx;cotx 1 sinxcosx −cotx;cotx$

20.

$1 1−cosx − cosx 1+cosx ;cscx 1 1−cosx − cosx 1+cosx ;cscx$

21.

$( secx+cscx )( sinx+cosx )−2−cotx;tanx ( secx+cscx )( sinx+cosx )−2−cotx;tanx$

22.

23.

24.

$tanx;secx tanx;secx$

25.

$secx;cotx secx;cotx$

26.

$secx;sinx secx;sinx$

27.

$cotx;sinx cotx;sinx$

28.

$cotx;cscx cotx;cscx$

For the following exercises, verify the identity.

29.

$cosx− cos 3 x=cosx sin 2 x cosx− cos 3 x=cosx sin 2 x$

30.

$cosx( tanx−sec( −x ) )=sinx−1 cosx( tanx−sec( −x ) )=sinx−1$

31.

$1+ sin 2 x cos 2 x = 1 cos 2 x + sin 2 x cos 2 x =1+2 tan 2 x 1+ sin 2 x cos 2 x = 1 cos 2 x + sin 2 x cos 2 x =1+2 tan 2 x$

32.

$( sinx+cosx ) 2 =1+2sinxcosx ( sinx+cosx ) 2 =1+2sinxcosx$

33.

$cos 2 x− tan 2 x=2− sin 2 x− sec 2 x cos 2 x− tan 2 x=2− sin 2 x− sec 2 x$

### Extensions

For the following exercises, prove or disprove the identity.

34.

$1 1+cosx − 1 1−cos(−x) =−2cotxcscx 1 1+cosx − 1 1−cos(−x) =−2cotxcscx$

35.

$csc 2 x( 1+ sin 2 x )= cot 2 x csc 2 x( 1+ sin 2 x )= cot 2 x$

36.

$( sec 2 (−x)− tan 2 x tanx )( 2+2tanx 2+2cotx )−2 sin 2 x=cos2x ( sec 2 (−x)− tan 2 x tanx )( 2+2tanx 2+2cotx )−2 sin 2 x=cos2x$

37.

$tanx secx sin( −x )= cos 2 x tanx secx sin( −x )= cos 2 x$

38.

$sec( −x ) tanx+cotx =−sin( −x ) sec( −x ) tanx+cotx =−sin( −x )$

39.

$1+sinx cosx = cosx 1+sin( −x ) 1+sinx cosx = cosx 1+sin( −x )$

For the following exercises, determine whether the identity is true or false. If false, find an appropriate equivalent expression.

40.

$cos 2 θ− sin 2 θ 1− tan 2 θ = sin 2 θ cos 2 θ− sin 2 θ 1− tan 2 θ = sin 2 θ$

41.

$3 sin 2 θ+4 cos 2 θ=3+ cos 2 θ 3 sin 2 θ+4 cos 2 θ=3+ cos 2 θ$

42.

$secθ+tanθ cotθ+cosθ = sec 2 θ secθ+tanθ cotθ+cosθ = sec 2 θ$

Order a print copy

As an Amazon Associate we earn from qualifying purchases.